The Impact of Economic Development of the Guangdong-Hongkong-Macao Greater Bay Area on Air Pollution: Investigation Based on Remote Sensing Data of Nighttime Lights and Air Pollution - Ji, Xiaole; Li, Shaoxing; Jiang, Na; Wang, Fei; Fan, Liya; Niu, Xiao (Frontiers in Marine Science, 2022)
Whether the Guangdong-Hongkong-Macao Greater Bay Area (GBA) can achieve the goal of environmental protection at the same time as its rapid economic development is an important issue that deserves attention. In this paper, we obtained remote sensing data on air pollution including CO, NO2, SO2, PM10, PM2.5, and nighttime light data. We combined the remote sensing data with county-level economic statistics to study economic development and air pollution in the Guangdong-Hongkong-Macao GBA. Our research showed that the economic development in the Guangdong-Hongkong-Macao GBA significantly increased the emissions of NO2, PM10, and PM2.5 and did not have significant effects on CO and SO2. We constructed an emission intensity indicator of pollutants per unit of luminance. We found that the unit emission intensity of four categories of pollutants, PM10, PM2.5, SO2, and CO, showed a significant decreasing trend in line with economic development. The emission intensity of NO2 showed a trend of first decreasing and then increasing. The conclusion of this research illustrates that the emission intensity of pollutants per unit of luminosity in the Guangdong-Hongkong-Macao GBA is continuously reducing. The emission of pollutants will gradually change from slow growth to zero growth. However, the emission of NO2 pollution should be an area of focus in achieving the dual goals of economic development and environmental protection.